Hubungan Asupan Pangan Lokal dengan Lingkar Lengan Atas pada Wanita Usia Subur di Wilayah Bendosari - Wafiy Lailin Prehamukti; Luluk Ria Rakhma; Muwakhidah, Muwakhidah (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Women of childbearing age are women who are still of reproductive age, ranging from 15 to 49 years old. Women of childbearing age are a group that is vulnerable to nutritional problems. One factor contributing to nutritional problems in women of childbearing age is inadequate nutritional intake. This nutritional intake can be obtained from consuming local foods, which can improve nutritional status. The objective of this study was to determine the relationship between local food intake and upper arm circumference in reproductive-age women in the Bendosari region. The research method used in this study was an observational analytical study with a cross-sectional design. A sample of 162 participants was selected using random sampling and adjusted according to inclusion criteria such as being aged 19–39 years, not currently pregnant, not currently on a diet, and willing to participate as respondents. Data on local food intake were obtained from the Semi-Quantitative Food Frequency SQ-FFQ form, while nutritional status was measured using upper arm circumference, a simple anthropometric indicator for assessing nutritional status, particularly muscle mass and body fat. This study used the Spearman's rank correlation test. The results showed a significant association between energy intake (p = 0.000), protein intake (p = 0.005), fat intake (p = 0.004), and carbohydrate intake (p = 0.000) with nutritional status. It can be concluded that dietary intake influences nutritional status.